Seleksi Risiko Pada Produk Surety Bond Era Pandemi Covid-19 Pada Pt. Bumiputera Muda 1967 - darwis harahap; Ahmad Afandi; Saadah Saadah; endah Rabiatul Adawiyah (UIN Sultan Maulana Hasanuddin Banten, 2023)
It is important for insurance companies to carry out a risk selection of the risks that exist in the insurance products offered carefully and thoroughly in order to avoid large losses due to claims. After the COVID-19 pandemic catastrophic event, the company became more vigilant about the risk selection process in each of its products, one of which is a surety bond product at the insurance company PT Bumiputera Muda 1967 Serang Branch. The underwriter is trained to be able to recognize every potential risk that exists in the prospective insured by carrying out the underwriting process effectively and accurately. In this study, it will be discussed about the underwriting procedures carried out by PT Bumiputera Muda 1967 Serang Branch in determining risk selection on surety bond products during the co-19 pandemic. The results of this study show that in surety bond products there are several stages, namely: The principal contacts the agent, the analysis process, data input, print the policy. Where there are 4 types of guarantees including bind bond, performance bond, advance payment bond, and maintenance bond. The obstacles faced by the underwriter are restrictions on surveys of field conditions, survey reports are additional requirements given by the underwriter in the risk selection process for surety bond products after the Covid-19 pandemic.